2014
DOI: 10.1097/igc.0000000000000141
|View full text |Cite
|
Sign up to set email alerts
|

Femoral Nerve Injury Complicating Surgery for Gynecologic Cancer

Abstract: Femoral nerve injury during gynecologic cancer surgery was associated with the Bookwalter retractor. The pelvic blades of the retractor may exert a compression on the nerve. The weakened muscles suggest that the nerve compression occurred intrapelvically over the iliacus muscle. Shortening the time of maximal traction of the pelvic blades reduced the incidence of femoral nerve injury. When performing gynecologic surgery with the use of the Bookwalter retractor, care must taken with the placement of the pelvic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Three of these studies were random control trials [5] [6] [7], two were retrospective and prospective analyses [8] [9] with the remaining five being retrospective analyses. Of these cases, two were chosen not to be included in the statistical summaries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three of these studies were random control trials [5] [6] [7], two were retrospective and prospective analyses [8] [9] with the remaining five being retrospective analyses. Of these cases, two were chosen not to be included in the statistical summaries.…”
Section: Resultsmentioning
confidence: 99%
“…In the two papers in which both retrospective and prospective data were collected, the incidence was 2.9% (statistically significant) [8] and 25% (statistically not significant) [9].…”
Section: Femoral Neuropathiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Further, an Australian study of 611 patients demonstrated that cytoreductive surgery can be successfully performed in the elderly with equally good results . Of note, femoral nerve injuries are not uncommonly reported after pelvic surgery in around 2% of cases . As use of retractors has previously been associated with the risk of nerve compression or impingement, we have employed gentle manual retraction and followed precise anatomical planes.…”
mentioning
confidence: 99%